Impact Product Knowledge and Lifestyle on Purchasing Decisions in Thriftshop in Indonesia with WOM Intervening Variable - Akmal, Muhammad Rafi; Firdaus, Firdaus (Universitas Islam Kadiri, 2026)
This study is driven by the growing trend of thrifting in Indonesia, which has gained momentum due to lifestyle shifts, increased awareness of sustainability, and more competitive product prices. However, consumers' decisions to purchase from thrift stores are influenced by multiple factors, with product knowledge, lifestyle, and word-of-mouth (WOM) being the most significant. This study looks at how product knowledge and lifestyle affect purchasing decisions, both directly and indirectly through interpersonal transmission functioning as an intermediary element. The study adopts a quantitative method utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM). A sample of 120 consumers of Indonesian thrift stores participated in the research. The The findings reveal that both product knowledge and lifestyle exert significant and positive influences on WOM communication as well as on consumers’ purchasing decisions. Additionally, WOM was found to positively influence purchase decisions and act as a bridge between product knowledge, lifestyle, and purchase decisions. These results show the importance of understanding products, matching lifestyles, and social recommendations in improving purchase decisions in the Indonesian thrift store market